Vascular endothelial growth factor ameliorates the ataxic phenotype in a mouse model of spinocerebellar ataxia type 1 - Cvetanovic, Marija; Patel, Jay M.; Marti, Hugo; Kini, Ameet R.; Opal, Puneet (Nature medicine, 2011)
Spinocerebellar ataxia 1 is a neurodegenerative disease caused by a CAG trinucleotide expansion in the ATXN1 gene encoding the protein ataxin-1. Puneet Opal and his colleagues find that ataxin-1 represses the expression of the angiogenic and neurotrophic factor vascular endothelial growth factor (VEGF) and that VEGF levels are decreased in animals with motor impairment. Overexpression or infusion of VEGF improves motor performance and pathology, suggesting VEGF may have therapeutic potential in this disease.